Plano de águas municipal como instrumento de política pública para universalização do abastecimento de pequenas comunidades rurais do semiárido cearense - Silva, Francisco Osny Enéas da (2011)
The search for a permanent solution to the problem of water supply for human consumption in small rural communities scattered in Brazilian semi-arid can be assessed by means of a public policy aimed at universalization and the sustainability of individual and collective systems of supply. It is argued in this survey that the most appropriate instrument to underpin this public policy would be the Municipal Water Plan-PAM, which consists of a focused vision of planning of water resources for small rural communities, especially those with population between 3 to 50 families. The Municipal Water Plan is based on a proactive action shared between civil society and public authorities to achieve universalization and the sustainability of these systems. The theoretical conceptualization and the methodological basis for the elaboration of a PAM is discussed in this thesis with reference to the pioneering plan of the municipality of Milhã in the State of Ceará, which formed the basis for construction of a public policy both within the municipal sphere as in the State sphere aimed at the universalization of the supply of rural communities of the municipality and with prospects of expanding to the rest of the State and probably can become an instrument applicable to the whole Brazilian Northeast.